Primary hepatic adenosquamous carcinoma: A rare case report - Dong Wei; Liu Lu; Chen Ying; Kang Qingsong; Li Dongbo; Li Feibo (Wolters Kluwer Medknow Publications, 2021)
Primary hepatic adenosquamous carcinoma (ASC) is an extremely rare primary hepatic malignant tumor, which is easily misdiagnosed as hepatocellular carcinoma before surgery. It has both the histologic features-adenocarcinoma and squamous cell carcinoma. Primary hepatic ASC incidence rate in intrahepatic cholangiocarcinoma is 2% to 3%.[1] Patients with hepatic ASC may experience recurrence or metastasis after surgery. The epidemiology, clinical diagnosis, etiology, and treatment of the disease remain challenging. It is important to improve the recognition of hepatic ASC because of its bad prognosis. Here, we report a man who had complained of an upper stomachache for 2 months and was diagnosed with primary hepatic ASC by histology and immunohistochemistry (IHC) after laparoscopic hepatectomy. The patient remained asymptomatic and survived well for 2 years post surgery and long-term follow-up was continued till now. In addition, we offer a brief discussion about the histopathological features, clinical behavior, and treatment of hepatic ASC and review the relevant literature.